Highly Sensitive Escherichia coli Shear Horizontal Surface Acoustic Wave Biosensor with Silicon Dioxide Nanostructures. (2017) - Ten, S.T.; Hashim, U.; Nordin, A.N.; Gopinath, S.C.B.; Liu, W.W.; Foo, K.L.; Sam, S.T.; Rahman, S.F.A.; Voon, C.H.
Abstract: In this study, a shear horizontal surface acoustic wave (SHSAW) was used for Escherichia coli ( E. coli ) detection. E. coli O157:H7 serotype, a dangerous strain among 225 E. coli unique serotypes was chosen as test sample. A few cells of this bacterium are able to cause young children to be most vulnerable to serious complications. Presence of higher than 1 cfu E. coli O157:H7 in 25 g of food has been considered as a dangerous level. The SHSAW biosensor was fabricated on 64 0 YX LiNbO3 substrate. Five different interdigital transducers (IDT) parameters (Fig. 1(a)-1(e)) SHSAW were fabricated to compare the mass loading sensitivity before advancing to the bio sensing application: four of them were 32 μm pitch size (with the average of synchronous frequency, f0 = 144.303 MHz) and one was 12 μm pitch size (with f0 = 384.948 MHz). All of the four 32 μm pitch sizes were with different combination of delay line length (3.904 mm and 7.296 mm) and aperture size (1.376 mm and 2.464 mm). As for the 12 μm pitch size device, it was with 2.1 mm delay line length and 0.72 mm aperture size. Eventually, 12 μm pitch size device was selected for oligonucleotides detection and its mass loading sensitivity was 1558.04 MHz/ (mg/mm 2 ), 4.8-fold higher than the most sensitivity one in 32 μm pitch size). Its sensitivity was enhanced by depositing 130 nm thin layer of SiO2 nanostructures with particle size less than 70 nm (Fig. 1(f)-1(g)). The nanostructures act both as a waveguide as well as the surface physical modification of the sensor prior to biomolecule immobilization. For this work, a specific DNA sequence from E. coli O157:H7 having 22 mers as an amine-terminated probe ssDNA was immobilized on the thin film sensing area through chemical functionalization [(CHO-(CH2)3-CHO) and (APTES; NH2-(CH2)3-Si(OC2H5)3]. The high-performance of sensor was shown with the oligonucleotide target and attained the sensitivity of 0.6439 nM/ 0.1 kHz and detection limit was down to 1.8 femtomolar (1.8 x 10 -15 M). Further evidence was provided by specificity analysis using single mismatched and complementary oligonucleotide sequences.